The Determinates of Hesitancy of Taking Covid-19 Vaccine in Jordan - Qablan, Ayat; Qablan, Almutazballlah; Gablan, Mohammad; Alhumoud, Tasnim; Amer, Ala’a Bani; Muzher, Besan; Zietoon, Nour; Al-Howari, Rama; Hawamdeh, Rmooz; Alamarat, Taima; et al. (Journal of Biology and Life Science, 2023)
This study aimed to identify the determinants that led to the hesitancy of taking the corona vaccine. In order to achieve the objective of the study, a questionnaire was distributed to residents in Irbid city. The study sample amounted to (519) residents selected according to a simple random sampling technique. The crosstab analysis and one sample T. test and regression analysis were used in order to test hypotheses of the study. The study reached many results, most notably: There is a statistically significant relationship between the hesitancy of taking the Corona vaccine and both ages, marital status, infection with the virus, taking the vaccine, and sources of information about the Corona virus. The combined determinants (beliefs and fears) explained (28.4%) of the hesitation in taking the Corona vaccine, and the remaining percentage that was not explained in this model is attributed to other independent variables that were not addressed in this study. The study recommended community members not to rely on social media sources as a source for obtaining information related to COVID-19 vaccine, especially as it is tainted by many rumours and errors.